USE OF DIFFUSION-WEIGHTED MAGNETIC RESONANCE IMAGING FOR REVEALING HYPOXIC-ISCHEMIC BRAIN LESIONS IN NEONATES - E. V. Shimchenko; E. I. Kleshchenko; K. F. Goloseyev (Педиатрическая фармакология)
The article presents advantages of use of diffusion-weighted magnetic resonance imaging (DW MRI) for revealing hypoxic-ischemic brain lesions in neonates. The trial included 97 neonates with perinatal brain lesion who had been undergoing treatment at a resuscitation department or neonatal pathology department in the first month of life. The article shows high information value of diffusion-weighted images (DWI) for diagnostics of hypoxic-ischemic lesions in comparison with regular standard modes. In the event of no structural brain lesions of neonates, pronounced increase in signal characteristics revealed by DWI indicated considerable pathophysiological alterations. Subsequently, children developed structural alterations in the form of cystic encephalomalacia with expansion of cerebrospinal fluid spaces manifested with pronounced neurological deficit. DW MRI has been offered as a method of prognosticating further neurological development of children on early stages.